Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2017)
The 10th anniversary of the worst downturn since the Great Depression finds the global economy at risk of a fresh crisis and ill-prepared for the disruption likely from the robot age, the World Economic Forum has warned.The body that organises the annual gathering of the global elite in Davos each January used its annual league table of competitiveness to stress that the failure to push through growth and productivity-friendly policies since the crash of 2007-08 had jeopardised chances of a sustained recovery.....